Primary chest wall sarcoma; a single institution experience of 3 years. (2021) - Gangopadhyay, Abhishek; Nandy, Kunal; Puj, Ketul; Sharma, Mohit; Jayaprakash, Dipin; Salunke, Abhijeet; Jain, Abhishek; Pandya, Shashank
Highlights: The current study is one of the largest series of chest wall sarcoma in whom surgical resection was performed. In the current series, the most common histopathologic type was ewing's sarcoma as compared to the western literature in which the most common type was chondrosarcoma. An algorithmic approach for the surgical management of defects formed following resection of chest wall tumor has been proposed which will be helpful for the surgeons in surgical planning of chest wall sarcoma cases. Frozen section analysis is very essential whenever in doubt to reduce margin compromise especially in ewings sarcoma. Survival analysis was performed separately for the major histopathological types. Abstract: Introduction: Primary chest wall sarcoma is a rare entity. It can be classified based on its origin, as bone sarcomas or soft tissue sarcomas. Various prognostic factors have been studied in different case series like age, sex, tumor histology, grade, resection margin status, adjuvant treatment, and others. The present study aimed to analyze common histological types, their management by resection and reconstruction and prognosis, in cases presenting at a regional cancer center in western India. Material and method: This was an observational study from a prospectively maintained database. 57 patients with chest wall sarcoma treated with curative intent between January 2016 till January 2019 with a minimum follow-up of 3 months were included in the study. The goals of surgical treatment were to obtain a wide resection margin of 3–4 cm, preserve the function of the chest wall and provide stability and rigidity to protect intrathoracic organs. Results: The median follow-up of the present patient's cohort was for 20.2 months. Overall two-year survival was 74.7%. Two-year OS and DFS of bone sarcoma were 62.3% and 35% and soft tissue sarcomas were 91% and 71.3%. Ewing's sarcoma had the worst two-year overall survival of 50.6% and chondrosarcoma and fibromatosis had 100% two-year overall survival. Conclusion: Chest wall sarcoma forms a heterogeneous group of tumors. In the present study, Ewing's sarcoma was the most common histology with the worst survival, since they presented in advanced stages. Management should be multidisciplinary and surgical resection should be aggressive to achieve an R0 resection. Reconstruction of chest wall should aim to provide structural and functional stability with minimal morbidity. Frozen section assessment should be utilized whenever in doubt.